Gender norms and social transformation of agriculture in Sub-Saharan Africa - Mapedza, Everisto D. (CRC Press, 2024)
There is a paucity of scientific information regarding gender norms and social transformation in the Sub-Saharan region. This has contributed to the insufficient articulation of gender issues in the proposed agricultural programmes and visions, such as the African Union’s Agenda 2063 and the Malabo Declaration. These efforts premise the transformation of the African continent on the foundation of the agricultural sector, a critical pillar in most countries in Sub-Saharan Africa. Global initiatives such as the Sustainable Development Goals (SDGs) of the United Nations and Climate Change of the United Nations Framework Convention on Climate Change must be locally applied. This means that the water and land livelihood pathways in agriculture and the related value chain linkages will contribute towards food self-sufficiency for Africa and the modernization of the economies in Africa. In all these discourses, whilst gender is sometimes highlighted, it is often not well articulated within the proposed solutions. This study aims to better understand the role of gender norms in agriculture transformation. This chapter aims to draw upon generic literature to illustrate how gender norms are central to transforming the agricultural sector within Sub-Saharan Africa. The study method is based on a generic desk study literature review that identified descriptive thematic areas.